Penerapan Model Pembelajaran Kooperatif Tife Course Review Horay (CRH) dengan Model Pembelajaran Langsung - Faisal Batennie (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2019)
The purpose of this study was to find out: Comparison of the results of the implementation of the cooperative model Course Review Horay type with direct learning in the assemblage material of class VII students of SMP 1 Kotabaru in the academic year 2017/2018. This study suggests an experimental research method is a study conducted by manipulating the object of research and the existence of control. This experimental method is often carried out in research, namely to investigate whether there is a causal relationship and how much the causal relationship is by giving certain treatments to several experimental groups and providing controls for comparison. Student learning outcomes by using the cooperative learning model Course Review Horay type in class VII material collections of SMP 1 Kotabaru in the 2017/2018 school year are in very good qualifications, with an average of 85.98. Student learning outcomes by using the direct learning model in the class VII material collection of the 1st Junior High School 1 in the 2017/2018 school year are in very good qualifications, with an average of 83.22. Noter can be a significant comparison between the learning outcomes of sperimen class students and control classes in class VII material set in 1 Kotabaru Junior High School in the school year 2017/2018. Keywords: Learning Kooperative, Type Course, Review Horay, Direct Learning